2010
DOI: 10.1089/ten.tea.2009.0238
|View full text |Cite
|
Sign up to set email alerts
|

Linear Shear Conditioning Improves Vascular Graft Retention of Adipose-Derived Stem Cells by Upregulation of the α5β1 Integrin

Abstract: Use of adult adipose-derived stem cells (ASCs) as endothelial cell substitutes in vascular tissue engineering is attractive because of their availability. However, when seeded onto decellularized vascular scaffolding and exposed to physiological fluid shear force, ASCs are physically separated from the graft lumen. Herein we have investigated methods of increasing initial ASC attachment using luminal precoats and a novel protocol for the gradual introduction of shear stress to optimize ASC retention. Fibronect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…Our laboratory has extensively studied the use of these cells to create an intimal surface on a natural vascular tissue conduit (decellularized vein graft). We have previously demonstrated that ASC acquire EC characteristics after culture in either endothelial cell growth supplement or in EGM2 [8e10, 26,27]; upregulate EC-specific markers in response to shear force [9]; and remain attached to the luminal surface of a vascular scaffold using flow conditioning to promote retention of the ASC [26]. In the present study, we evaluate the creation of the graft using ASC from DM patients.…”
Section: Discussionmentioning
confidence: 96%
“…Our laboratory has extensively studied the use of these cells to create an intimal surface on a natural vascular tissue conduit (decellularized vein graft). We have previously demonstrated that ASC acquire EC characteristics after culture in either endothelial cell growth supplement or in EGM2 [8e10, 26,27]; upregulate EC-specific markers in response to shear force [9]; and remain attached to the luminal surface of a vascular scaffold using flow conditioning to promote retention of the ASC [26]. In the present study, we evaluate the creation of the graft using ASC from DM patients.…”
Section: Discussionmentioning
confidence: 96%
“…The segments were decellularized by incubation in 0.075% sodium dodecyl sulfate for 15 h, leaving the vascular basement membrane and extracellular matrix intact, as previously described by us. 23 Decellularized vein segments were opened longitudinally and pinned lumen side up within a seeding chamber. Cells were seeded onto the surface of the vascular basement membrane at 4Â10 5 cells=cm 2 and incubated at 378C for up to 24 h. Cell attachment was quantified indirectly by counting the number of residual cells in the seeding medium after gentle washing with PBS.…”
Section: Attachment Studiesmentioning
confidence: 99%
“…The effect of shear force on cell retention after seeding onto a decellularized vein was determined using a bioreactor and flow conditioning system (Lab VIEW; National Instruments) as described by McIlhenny et al [23]. Briefly, the luminal surface of a decellularized human saphenous vein (5 cm in length) was precoated with fibronectin (18 mg=mL; BD Bioscience) for 1 h at 378C with rotation.…”
Section: Attachment Studiesmentioning
confidence: 99%
“…Activated ERK1/2 and PKA can activate transcription factors, such as Runx2 and AP-1, which can promote the transcription of osteogenic differentiation special genes (Kleiveland et al 2008) important in the osteogenic differentiation of hMSCs. FSS can up-regulate the level of α5β1 in human adipose-derived MSCs (McIlhenny et al 2010). Meanwhile, integrin α5β1 has been demonstrated to have an important role in the regulation of MSC osteogenic differentiation in 2D and 3D culture (Martino et al 2009).…”
Section: Integrin and Integrin-associated Kinasementioning
confidence: 99%